Strategi Pembelajaran Baca Tulis Al-Qur'an Masa Pandemi Covid-19 Bagi Siswa Kelas V SDN Kaliwungu 3 Kabupaten Semarang - Maslihatul Umami (Peneliti.net, 2022)
The object of study of this research is the BTQ Learning Strategy during the Covid-19 Pandemic for Class V Students with Case Studies at SD Negeri Kaliwungu 3, Kaliwungu district, Semarang Regency. This study aims to describe and analyze strategies, analyze the steps for implementing learning strategies, implementing BTQ learning strategies during the Covid-19 Pandemic for Student V at SD Negeri Kaliwungu 3 Kaliwungu district, Semarang Regency. In this study, the author uses a qualitative approach. This type of research is case research, case studies are interested in what is, take actions or controls that are carried out in order to get the causal meaning. In this research design there are three stages to be achieved by researchers, namely the pre-field (observation) stage, the field stage and the reporting stage. The results of this study are, (1) the teacher's strategy in delivering the material for reading and writing the Qur'an using powerpoint media makes children more enthusiastic in receiving the material, while in delivering material with a handbook makes children less enthusiastic in understanding what the teacher says. through WhatsApp video-call media, (2) the implementation of BTQ learning during the pandemic was carried out online, with the teacher's steps providing material through a whatsapp group, then conducting a videocall to explain the material, (3) evaluations in learning to read and write the Qur'an are reading fluency, writing accuracy, and recitation accuracy. Therefore, it is carried out verbally and also in writing. Keyword: Learning Strategies, BTQ, Covid-19 Pandemic Period.